On the Impossibility of Fair Risk Allocation - Péter Csóka; Péter Miklós Pintér (Hungarian Academy of Sciences, Institute of Economics, 2011)
Measuring and allocating risk properly are crucial for performance evaluation and internal capital allocation of portfolios held by banks, insurance companies, investment funds and other entities subject to financial risk. We show that by using coherent measures of risk it is impossible to allocate risk satisfying the natural requirements of (Solution) Core Compatibility, Equal Treatment Property and Strong Monotonicity. To obtain the result we characterize the Shapley value on the class of totally balanced games and also on the class of exact games. Our result can also be seen as a downside of coherent measures of risk.
Keywords: C71; G10; 330; Coherent Measures of Risk; Risk Allocation Games; Totally Balanced Games; Exact Games; Shapley value; Solution core; Risikomaß; Risikomanagement; Shapley-Wert; Spieltheorie